Food Crop Diversity, Women's Income-Earning Activities, and Distance to Markets in Relation to Maternal Dietary Quality in Tanzania. Issue 1 (26th November 2020) - Madzorera, Isabel; Blakstad, Mia M; Bellows, Alexandra L; Canavan, Chelsey R; Mosha, Dominic; Bromage, Sabri; Noor, Ramadhani A; Webb, Patrick; Ghosh, Shibani; Kinabo, Joyce; Masanja, Honorati; Fawzi, Wafaie W
ABSTRACT: Background: Women's dietary diversity and quality are limited in low- and middle-income countries (LMICs). Nutrition-sensitive interventions that promote food crop diversity and women's access to income could improve diets and address the double burden of malnutrition in LMICs. Objectives: We examined the associations among food crop diversity and women's income-earning activities with women's diet quality, as well as effect modification by access to markets, in the context of small-holder food production in rural Tanzania. Methods: Data from a cross-sectional study of 880 women from Rufiji, Tanzania, were analyzed. Women's dietary intake was assessed using a food frequency questionnaire. The prime diet quality score (PDQS; 21 food groups; range, 0–42), a unique diet-quality metric for women that captures the healthy and unhealthy aspects of diet, was computed. Generalized estimating equation linear models were used to evaluate the associations of food crop diversity and women's income-earning activities with PDQS, while controlling for socio-economic factors. Results: Maternal overweight (24.3%) and obesity (13.1%) were high. The median PDQS was 19 (IQR, 17–21). Households produced 2.0 food crops (SD ± 1.0) yearly. Food crop diversity was positively associated with PDQS ( P < 0.001), but the association was strengthened by proximity to markets ( P for interaction = 0.02). For women living close (<1.1 km) to markets, producing 1 additional food crop was associated with a 0.67 (95% CI, 0.22–1.12) increase in PDQS, versus a 0.40 (95% CI, 0.24–0.57) increase for women living farther away. The PDQS increased with women's salaried employment (estimate, 0.96; 95% CI, 0.26–1.67). Conclusions: Household food production may interact with access to markets for sales and purchases, while nonfarm income also improves women's diet quality in rural Tanzania. Programs to improve women's diet quality should consider improving market access and women's access to income (source of empowerment), in addition to diversifying production.